TEORI- TEORI BELAJAR UNTUK KECERDASAN BAHASA ANAK USIA DINI - Lydia Margaretha (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Learning theory raised by educational psychologists after they have difficulty to explain the whole learning process Implementation of Early Childhood Education at this time can not be separated from the theories presented by experts, both psychologists, philosophers, and observers of education. These theories greatly assist teachers today in dealing with the Early Childhood, the methods to do to teach children, and how to deal with children and their behaviors.On the above issues, the purpose of this paper is: Knowing what Tiori is used in the implementation of language education in children in early childhood Dahlia Kota Bengkulu.The method used a qualitative method. Research location in Early Childhood Dahlia Kota Bengkulu. Data collection using interviews, observation, and documentation. Research results show: Theory learning that is used in Early Childhood Dahlia integrated in every material, But Learning Theory for language intelligence in processing Words become a mainstay in educating children in early childhood Dahlia Bengkulu City.